1997
DOI: 10.1007/bf02801328
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to coumestrol, a phytoestrogen, does not alter spermatogenic potential in rats

Abstract: The objective of this study was to determine the effects of neonatal exposure to phytoestrogens on male reproductive function as adults. Male rats were injected either with 100 micrograms coumestrol or DMSO (controls) daily during their first 5 d of life. Pituitary gland, testes, sex accessory organs, and blood were collected on d 60 of life. Serum testosterone, LH, and FSH levels were determined by RIA. Levels of steady-state mRNA for gonadotrophin subunits (LH beta and FSH beta were determined by Northern bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
3
8
2
Order By: Relevance
“…In mammals (rats) the same effects of dietary phytoestrogens on the male reproductive tract have been noted (Atanassova et al, 2000;Delclos et al, 2001;Weber et al, 2001;Wisniewski et al, 2003). In contrast, no effects were observed for dietary genistein (Nagao et al, 2001;Fritz et al, 2003) or coumestrol (Awoniyi et al, 1997). In our study, we observed no differences in basal and LH-stimulated testosterone secretion by Leydig cells from ganders fed both control diets and diets with a higher phytoestrogen content.…”
Section: Discussioncontrasting
confidence: 60%
“…In mammals (rats) the same effects of dietary phytoestrogens on the male reproductive tract have been noted (Atanassova et al, 2000;Delclos et al, 2001;Weber et al, 2001;Wisniewski et al, 2003). In contrast, no effects were observed for dietary genistein (Nagao et al, 2001;Fritz et al, 2003) or coumestrol (Awoniyi et al, 1997). In our study, we observed no differences in basal and LH-stimulated testosterone secretion by Leydig cells from ganders fed both control diets and diets with a higher phytoestrogen content.…”
Section: Discussioncontrasting
confidence: 60%
“…The results of the study showed no significant body weight gain, also like in other studieswhere no significant differences in the animal body weights were observed (Awoniyi et al, 1997). Ukwenya et al, that profertility effects of alcoholic extract of sesame in male sprague-dawley rats studied, they found that the effects of ethanolic extract of beniseed (sesame) at 3000 mg/kg body weight, with vitamin C administered as adjuvant, have shown that beniseed has a potential to increase mean body weights of rats.…”
Section: Serum Hormone (Lh Fsh and T) Levelssupporting
confidence: 85%
“…In this context, epididymal and testicular sperm counts were not altered in rats administered genistein orally at doses of 12.5-100 mg/kg on postnatal days 1-5 (Nagao et al, 2001), 10-1000 μg/day (Shibayama et al, 2001) or 100 μg/day of coumestrol (Awoniyi et al, 1997). This was also true in rats chronically administered genistein at a dose of 50 μg/day (Roberts et al, 2000), 0.1-10 mg/kg/day through pregnancy and lactation (Fielden et al, 2003), 200 and 2000 mg of genistein per kg of diet for 12 months (Faqi et al, 2004) or 2.5 mg/kg/day for 5 months (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 85%